Clinical features of benign paroxysmal positional vertigo in the elderly - Ran Zhou; Huan Wang; Jiachen Shan; Chengcheng Li; Lin Han; Lin Han (Frontiers in Neurology)
ObjectivesThe typical age of benign paroxysmal positional vertigo (BPPV) is between 50 and 60 years. With the development of diagnostic techniques and the growth of the elderly, the number of elderly patients has been on the rise gradually. This study compared the clinical characteristics, treatments, and prognoses with patients.MethodsPatients were divided into two age groups based on age at onset of the disease: middle-aged BPPV (50–59 years) and elderly BPPV (60–80 years old). We compared clinical characteristics, treatment, prognosis, BPPV location, questionnaires between the two groups.ResultsFemale patients constituted a high proportion in both the middle-aged BPPV group (21, 75.0%) and the elderly BPPV group (39, 67.2%). The elderly group had significantly higher median scores in the DHI impact than the middle-aged group (24 vs. 16, p = 0.008). In contrast, the BBS score decreased (44 vs. 49, p = 0.019), and the elderly group exhibited higher fall rates (6.9% vs. 0%, p = 0.381) at the last follow-up. However, the elderly BPPV group had lower rates of maneuver (82.8% vs. 89.3%, p = 0.638). Age at onset was positively correlated with the DHI score (r = 0.316, p = 0.005) and negatively correlated with the BBS score (r = −0.330, p = 0.002).ConclusionCompared to the middle-aged BPPV group, elderly patients with BPPV exhibited a higher DHI score, increased fall rates, lower BBS scores, and lower rate maneuver, which had a more significant negative impact on daily life.